HUBUNGAN ANTARA INDUKSI PERSALINAN DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RUMAH SAKIT MARGONO SOEKARJO PURWOKERTO - Hartati -; Lutfatul Latifah Latifah; Adrianus Anjar Purbyuwono Purbyuwono (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2013)
The incidence of asphyxia in newborns can be caused by various factors including the factors that are not normal delivery or induction pesalinan. Induction of labor is only done if the mothers have obstetric problems or if the mother and baby have a medical problem. to accurately determine the maturity of the fetus, prior to induction, an amniocentesis can be done. The aim of this study is to determine the relationship between the induction of labor with the incidence of asphyxia neonatorum in RSUD Margono Soekarjo Purwokerto. This type of descriptive analytic study with case-control approach. The study population was infants born at the Hospital Margono Soekarjo Navan in January-June 2011, 173 babies are born asphyxiated and recorded in medical records. The number of samples used in this study is 43 samples and carried out 43 studies to determine the control group, so a total of 86 samples. Univariate analysis using frequency distribution and bivariate analsisis using Chi Square statistical test. Age mother mostly between the ages of 20-35 years both in the case group (88.4%) and controls (76.7%). Parity most of primiparous mothers in both groups of cases (52.2%) and in the control group (62.8%). Induction of labor with the majority of infants with birth asphyxia (% 62.8). Mothers who do not induce labor maternity largely normal delivery (62.8%). There is a relationship between the induction of labor with the incidence of neonatal asphyxia (p = 0.031). OR = 2.848 means that the value of labor induction at risk of having a baby with asphyxia 2.848 times greater than that without the induction of labor. Induction of labor significantly associated with incidence of asphyxia neonatorum. Keywords: Induction, labor, asphyxia